A History of Social Work in Public Health - Ruth, Betty J. (Am J Public Health, 2017)
Social work is a core health profession with origins deeply connected to the development of contemporary public health in the United States. Today, many of the nation’s 600 000 social workers practice broadly in public health and in other health settings, drawing on a century of experience in combining clinical, intermediate, and population approaches for greater health impact. Yet, the historic significance of this long-standing interdisciplinary collaboration—and its current implications—remains underexplored in the present era. This article builds on primary and contemporary sources to trace the historic arc of social work in public health, providing examples of successful collaborations. The scope and practices of public health social work practice are explored, and we articulate a rationale for an expanded place for social work in the public health enterprise.